Spin Challenge as an Educational Media to Increase Disaster Mitigation Knowledge in Elementary School Students - Bekti, Joko Tigo Narimo; Maryana, Maryana; Noamperani, Sapta Rahayu (Sekolah Tinggi Ilmu Kesehatan Kendal, 2024)
Lack of mature preparation related to disaster mitigation, low disaster response performance, and lack of introduction of disaster reduction education in the education sector are major disaster vulnerability issues in Indonesia.The need for disaster preparedness must be strengthened, especially for children. Children are one of the most vulnerable and often forgotten groups when disaster strikes. For this reason, children need to be involved in disaster mitigation activities through disaster mitigation education. Efforts to increase knowledge of disaster mitigation in children can be done using Spin Challenge educational game media. To determine how effective the Spin Challenge is as an educational medium to enhance the knowledge of elementary school students, this experimental study was conducted with a control group with pre-test and post-test. 82 students selected with a total sample approach were used as respondents in this study. Questionnaires on disaster mitigation are used to obtain data. In this study, the statistical tests used were the Mann-Whitney test and the Wilcoxon test. There are significant differences in knowledge levels (p-value = 0.000) of disaster mitigation before and after students were given disaster mitigation education using Spin Challenge educational media. There is an influence on the level of knowledge of disaster mitigation after children get disaster mitigation education using the educational game medium Spin Challenge.